Energy-saving potential evaluation for primary schools with occupant-centric controls. (1st July 2021) - Ye, Yunyang; Chen, Yan; Zhang, Jian; Pang, Zhihong; O'Neill, Zheng; Dong, Bing; Cheng, Hwakong
Abstract: Recent studies demonstrated that there is significant energy-saving potential for primary schools, which heating, ventilation, and air-conditioning (HVAC) systems with occupant-centric control (OCC) is an excellent candidate to save energy. However, such an energy impact has yet to be evaluated for different climate zones as well as different energy code versions, but is critical for technology transfer and deployment. Therefore, this paper conducts comprehensive evaluation on the energy-saving potentials for the primary schools with two advanced OCC strategies: presence-based and counting-based. Ninety-six building energy models with stochastic behavior of occupants are developed and simulated, which consist of two building energy code versions, 16 climate zones, and baseline case (without OCC) and two advanced cases (with OCC). To evaluate the energy saving potentials for OCC, primary schools in the U.S. are used as an example. The results show that there is significant energy-saving potential for primary schools by considering OCC strategies, especially the counting-based case. The energy-saving potential is up to 10.2% for presence-based OCC and 12.41% for counting-based OCC. Furthermore, both climate and code version have a significant impact on energy savings from OCC strategies. The energy-saving potentials vary from 1.79% to 12.41% for different climates and code versions. This evaluation can also contribute to quantify the nationwide energy saving potential for other countries. Highlights: Enhance building models by stochastic behavior of occupant presence and movement. Develop and implement zone and system-level occupant-centric controls. Study two code versions, 16 climate zones, and two types of occupant-centric control. Quantify savings of occupant-centric controls on school buildings.